Neurophysiological correlates of linearization in language production - Habets, Boukje (BioMed Central, 2008)
BACKGROUND: During speech production the planning of a description of several events requires, among other things, a verbal sequencing of these events. During this process, referred to as linearization during conceptualization, the speaker can choose between different types of temporal connectives such as 'Before' X did A, Y did B' or 'After' Y did B, X did A'. To capture the neural events of such linearization processes, event-related potentials (ERP) were measured in native speakers of German. Utterances were elicited by presenting a sequence of two pictures on a video screen. Each picture consists of an object that is associated with a particular action (e.g. book = reading). A coloured vocalization cue indicated to describe the sequence of two actions associated with the objects in chronological (e.g. red cue: 'After' I drove the car, I read a book) or reversed order (yellow cue). RESULTS: Brain potentials showed reliable differences between the two conditions from 180 ms after the onset of the vocalization prompt, with ERPs from the 'After' condition being more negative. This 'Before/After' difference showed a fronto-central distribution between 180 and 230 ms. From 300 ms onwards, a parietal distribution was observed. The latter effect is interpreted as an instance of the P300 response, which is known to be modulated by task difficulty. CONCLUSION: ERPs preceding overt sentence production are sensitive to conceptual linearization. The observed early, more fronto-centrally distributed variation could be interpreted as involvement of working memory needed to order the events according to the instruction. The later parietal distributed variation relates to the complexity in linearization, with the non-chronological order being more demanding during the updating of the concepts in working memory.